ADVANTAGES OF STUDYING THE DECISIONS AND PROGRAMS TAKEN BY REGIONAL AUTHORITIES ON TRAINING OF RESERVE PERSONNEL - Akbarov Sodiqjon Saxodullayevich (Modern American Journals, 2025)
The process of studying the decisions and programs taken by the regional authorities for the training of reserve personnel offers many advantages. These programs are aimed at training the skilled personnel who contribute to the economic and social development of the region. At the same time, this process helps to train competitive specialists in various industries, increases the efficiency of management and strengthens the personnel reserve. In this way, the regions will achieve sustainable and consistent upswing in economic development.
Keywords: Reserve personnel Regional management Personnel training Decisions Programs Development strategy Social management Staff development Policy Education policy Labor market.